Wybory językowe a złożona tożsamość – na przykładzie Żydów z dziewiętnastowiecznego Wrocławia - Rybińska, Agata (Studia Europaea Gnesnensia, 2014)
The purpose of this article is to illustrate the process of language change in the 19th-century Breslau. The analysis of four areas: education, literature, liturgy and onomastic data from grave inscriptions point to choices between two languages and partial linguistic acculturation, as well as testify to the complex identity of Breslau Jews.